MSME 5.0: Digital Entrepreneurship Using The Pentahelix Model - Bohaiki, Bohaiki; Isnaini, Teuku; Rozali, Rozali (LPPM Universitas PGRI Sumatera Barat, 2024)
The development of MSMEs 5.0 in the economic aspect of digitalization must adapt to industrial advances that are increasingly coexisting with technology. As a government program that wants to advance business actors in the current digital era, by educating MSME players. For this reason, it is necessary to collaborate or the role of figures (pentahelix) aims to see the development of Digital-based MSMEs, to see the role of stakeholders in the Pentahelix model and to see the strategy for developing Digital MSMEs. The type of research that will be used in this research is qualitative which is inductive analysis by collecting, compiling and describing various data, and actual information and using SWOT analysis from academics, business people, government, communities and media conducted in Banda Aceh City.